2018
DOI: 10.1002/clc.23051
|View full text |Cite
|
Sign up to set email alerts
|

Right atrial function by speckle tracking echocardiography in atrial septal defect: Prediction of atrial fibrillation

Abstract: Two-dimensional and three-dimensional speckle tracking echocardiography was clinically helpful in ASD patients in revealing right atrial dilatation and dysfunction pre-existent to device closure and associated with PAF development. RA parameters had a higher association with PAF compared to both the size of the implanted device and left atrial indices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 27 publications
0
31
0
2
Order By: Relevance
“…RA dysfunction may cause POAF development with mechanisms similar to LA dysfunction because they share the same embryonic origin and cellular structure. 9,22,27,28 During the evaluation of the RA by deformation analyses, conduit, reservoir, and contraction functions can be calculated. RASr is the most commonly studied of these functions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…RA dysfunction may cause POAF development with mechanisms similar to LA dysfunction because they share the same embryonic origin and cellular structure. 9,22,27,28 During the evaluation of the RA by deformation analyses, conduit, reservoir, and contraction functions can be calculated. RASr is the most commonly studied of these functions.…”
Section: Resultsmentioning
confidence: 99%
“…Myocardial fibrosis plays a key role in POAF development . AF might develop after percutaneous patent foramen ovale closure, and in relation with the progression of the remodeling process …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22) Using this method, we evaluated speckle tracking in patients with ASD. 23,24) After one cardiac cycle was selected, we selected the septal and lateral corners of the mitral annulus and the LA roof in the systolic frame. The QLAB software automatically provided seven tracking regions on the LA wall and calculated the longitudinal strain (LS) using speckle tracking.…”
Section: Figurementioning
confidence: 99%
“…2D speckle tracking analysis has been widely used to evaluate ventricular function, 15 As a study conducted in adults reported that the RA strain during the reservoir phase is a predictor of atrial fibrillation development 17 , the possibility of future arrhythmias in the Operation and Device groups with decreased εS may be considered. Therefore, ASD patients treated under 5 years of age require long-term follow-up with the possibility of arrhythmia and reduced atrial function.…”
Section: Conventional Echocardiographic Indicatorsmentioning
confidence: 99%